013 Acute ischaemic brain lesions in intracerebral haemorrhage: multicentre cross-sectional MRI study. Issue 3 (9th February 2012) - Werring, D; Gregoire, S M; Charidimou, A; Gadapa, N; Dolan, E; Antoun, N; Peeters, A; Vandermeeren, Y; Laloux, P; Baron, J C; Jager, H R
Abstract : Background: Subclinical acute ischaemic lesions have recently been described in spontaneous intracerebral haemorrhage (sICH). We hypothesised that they are related to MRI markers of small vessel disease [SVD] (hypertensive arteriopathy or cerebral amyloid angiopathy [CAA]) in a multicentre, cross-sectional study. Methods: We studied consecutive patients with sICH from four stroke centres, and age-matched stroke referrals without sICH. Acute ischaemic lesions were assessed on MRI (<3 months post-sICH) using diffusion-weighted imaging (DWI). White matter changes (WMC) and cerebral microbleeds (CMBs) were rated. We investigated associations between DWI lesions, clinical and radiological characteristics. Results: We included 114 sICH patients (39 with probable CAA); and 47 controls. The prevalence of DWI lesions was 9/39 (23%) in probable CAA-related ICH vs 6/75 (8%) in the remaining patients with sICH (p=0.024); no DWI lesions were found in controls. DWI lesions were associated with WMC score (OR 1.14 per unit increase, p=0.024) and strictly lobar CMBs (OR 3.85, p=0.029). Conclusion: Acute, subclinical ischaemic brain lesions are frequent after sICH, and three times more common in CAA-related ICH than in other ICH types. They are associated with WMC and CMBs, suggesting that they result from an occlusive small vessel arteriopathy. They contribute to the overall burden of vascular-related damage in ICH, and may be a useful surrogate marker of ongoing ischaemic injury from SVD.